ENZYMATIC ACTIVITY OF WOOD DEGRADING -BASIDIOMYCETES Pleurotus ostreatus UZBI-105 IN THE VARIOUS CARBON SOURCES - Akhmedova Z. R; Rashidova N.T (Journals Park Publishing, 2022)
Basidiomycetes have not only high nutritional value, but also serve as a source of biologically active substances. One of the promising areas of bioconversion of plant substrates are the technology of IP-use of wood-basidiomycetes [1].
Keywords: lignocellulosic wastes, Pleurotus ostreatus, production, enzymes